PEMBUATAN GAME EDUKASI TERMINOLOGI MEDIS MENGGUNAKAN KAHOOT BAGI MAHASISWA SEMESTER 2 PROGRAM STUDI D3 RMIK POLTEKKES KEMENKES MALANG - Dwi Sintawati Nur Mahmudah; Dea Allan Karunia Sakti (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
Medical terminology becomes an important course because it supports the main competence of medical recorders as a clinical coder. The number of medical terms studied requires students to practice more by utilizing various learning media. Digital Game Base Learning is a method of blending learning and playing patterns by utilizing computer devices and smartphones, this is expected to bring joy, increase the enthusiasm of learners in the learning process and grow the power of competition. This study aims to determine the acceptance or response of students to the use of Kahoot as a medium of exercise in medical terminology courses. The type of research used is qualitative research. The informants in this study were 15 2nd semester students at the D3 RMIK Poltekkes Study Program of the Ministry of Health Malang. The research instruments used are interview guidelines and Kahoot quiz questions. Quiz results are analyzed descriptively and interview results are transcribed by general findings. The results of this study are (1) identification of educational game needs using Kahoot including mobile phones, laptops, internet networks, materials and medical terminology questions, (2) all students respond positively to the innovation of using Kahoot as one of the training media of medical terminology.